Stimulasi stres dan strategi daya tindak dalam kalangan pesakit kegagalan renal peringkat akhir yang menjalani rawatan hemodialisis dl Hospital Universiti Sains Malaysia (HUSM) - Masliza, Tuda
This is quantitative descriptive study that identifies stressor and coping strategy among end stage renal failure (ESRF) patient receiving hemodialysis treatment in Hospital of University Science Malaysia (HUSM). This study also identifies the relationship between stress level and coping strategy among ESRF patient as well as the relationship between socio-demographic factor such as gender, age, socioeconomic status, education level and duration of treatment. The subjects included 17 patients who undergoing chronic hemodialysis in Hemodialysis Unit, HUSM. This is cross sectional study designed using non probability purposive sampling which used questionnaire as instrument that adapted from Hemodialysis Stressor Scale (HSS) and Jaloweic Coping Scale (JCS). Reliability testing to HSS and JCS was done and demonstrate value that satisfied (a = 0.79 for HSS and a = 0.77 for JCS). Analysis of data use SPSS version 12 with application descriptive statistics, Pearson colerration, independent t-test and ANOVA's test to answer research questions. Findings showed level of stress (mean = 47.76, SO = 10.53) and application of coping strategy (mean = 76.59, S0=14.44) in circle patient is average levels. Five of most identified stressors that have been are vacation limitation (mean = 2.29, SO = 0.85), water restriction (mean = 2.24, SO = 0.66), cost factors (mean = 2.06, SO = 0.83), activity limitation (mean = 2.06, SO = 0.75) and food restriction (mean = 1.82, SO = 0.73). Meanwhile, the most commonly used coping strategies were belief in God (mean = 3.06, SO = 1.30), resolve problems as much as could (mean= 3.06, SD = 1.09), told yourself there are other people had worse luck than you (mean = 2.88, SO = 1.05), mediatation or any activity to induce calm (mean = 2.76, SD = 0.97), do everything with your best (mean = 2.71, SD = 1.31). There are no significant difference between level of stress and coping strategies used (r = 0.16, p>0.05). Meanwhile coping strategies level is influenced by education level (p = 0.01) and socioeconomic status (p = 0.04). In conclusion, the nurses need to stress on education and socioeconomic level during promoting coping strategy among ESRF patients receiving hemodialysis treatment. In short, stres and coping strategies levels in circle patient is average. Although no association between the level stres and level of coping strategies, ESRF's patient experience stressors certain caused haemodialysis disease and treatment and choose certain coping strategies. In addition, education factor and status socioeconomic influence application of copind strategies show nurse must supply more information to the patient relating treatment and development of health and promote coping strategies suitably to enhance the capability patient adaptation life so that well-being optimised.